Developing Innovative Nanomaterials as Adsorbents for Water Treatment and their Environmental Impact - Mohanty, Sarat Chandra; Jana, Anup Kumar (Migration Letters, 2023)
Water treatment is paramount in tackling the increasingly pressing environmental issues associated with water contamination. The present study investigates the progression of novel nanomaterials as exceptionally effective adsorbents for water purification while also evaluating their potential ecological consequences. The significance of water treatment cannot be overstated when it comes to protecting the environment and ensuring public health. This is due to the intricate and varied pollutants that are brought into water sources from many sources of waste, such as household, industrial, and environmental concerns. Adsorbents are crucial in capturing and immobilizing contaminants, making them essential instruments in this particular setting. Nanomaterials have garnered attention as potential adsorbents owing to their notable specific surface area and adjustable features. These materials possess a large surface area, reactivity, and configurable surface chemistry, rendering them intriguing candidates for adsorption applications. This manuscript presents the Innovative Nanoparticles for Water Treatment Framework (INM-WTF). This innovative approach utilizes state-of-the-art nanoparticles to improve water treatment processes’ efficiency significantly. The outcomes of the INM-WTF experiment include the following parameters: Pollutant Removal Efficiency of 96.5%, Permeate Flux of 395 L/m²h, Adsorption Capacity of 155 mg/g, Photocatalytic Degradation Rate of 85%/hour, Membrane Filtration Efficiency of 97.5%, and Water Quality Compliance of 1.7 µg/L. The results indicate significant progress in water treatment capabilities, emphasizing nanomaterials’ potential to tackle environmental issues, enhance water quality, and guarantee adherence to rigorous regulatory benchmarks.